2017
DOI: 10.1007/s00592-017-1051-5
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy lifestyle habits and diabetes-specific health-related quality of life in youths with type 1 diabetes

Abstract: The clustering of unhealthy lifestyle habits is associated with reduced HRQoL in adolescents and young adults with T1DM. Promoting multiple behavior changes may be a useful approach to improve the health status and the HRQoL in youths with T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 43 publications
1
35
1
17
Order By: Relevance
“…There is only one cross-sectional study that has been performed with young people with T1D (from 13 to 19 years old) that associated diabetes-specific QoL with the MedDiet pattern [7]. The researchers did not find any relationship between the MedDiet and QoL in this population, a finding that is in contrast with our results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There is only one cross-sectional study that has been performed with young people with T1D (from 13 to 19 years old) that associated diabetes-specific QoL with the MedDiet pattern [7]. The researchers did not find any relationship between the MedDiet and QoL in this population, a finding that is in contrast with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Scientific evidence has shown that the presence of cardiovascular diseases and late diabetic complications have a negative impact on the quality of life (QoL) and treatment satisfaction (TS) of people with T1D [6]. Furthermore, a study performed in children and adolescents (between 13 and 19 years old) described that insulin treatment and dietary limitations in the management of T1D may have several effects on QoL [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration of predictors related to improvement of individuals over time could help to improve resilience and could facilitate to develop measures to improve HRQL of children with T1DM. Previous research found that unhealthy lifestyle habits, such as diet and low physical activity, are associated with lower HRQL (52). Promoting healthy life style habits in children with T1DM could be an important aspect to improve HRQL over time.…”
Section: Discussionmentioning
confidence: 99%
“…No se han encontrado otros estudios que aborden este aspecto.5.4.7. Otros factoresEstudios como el de Mozzillo et al121 sugieren que pacientes que siguen estilos de vida poco saludables: comportamiento sedentario, baja realización de actividad física o no siguen dieta mediterránea, entre otros factores, tienen peor CVRS.…”
unclassified